Highly Stable Gully-Network Co3O4 Nanowire Arrays as Battery-Type Electrode for Outstanding Supercapacitor Performance - Guo, Chunli; Yin, Minshuai; Wu, Chun; Li, Jie; Sun, Changhui; Jia, Chuankun; Li, Taotao; Hou, Lifeng; Wei, Yinghui (Frontiers in Chemistry, 2018)
3D transition metal oxides, especially constructed from the interconnected nanowires directly grown on conductive current collectors, are considered to be the most promising electrode material candidates for advanced supercapacitors because 3D network could simultaneously enhance the mechanical and electrochemical performance. The work about design, fabrication, and characterization of 3D gully-network Co3O4 nanowire arrays directly grown on Ni foam using a facile hydrothermal procedure followed by calcination treatment will be introduced. When evaluated as a binder-free battery-type electrode for supercapacitor, a high specific capacity of 582.8 C g-1 at a current density of 1 A g-1, a desirable rate capability with capacity retention about 84.8 % at 20 A g-1, and an outstanding cycle performance of 93.1 % capacity retention after 25,000 cycles can be achieved. More remarkably, an energy density of 33.8 W h kg-1 at a power density of 224 W kg-1 and wonderful cycling stability with 74 % capacity retention after 10,000 cycles can be delivered based on the hybrid-supercapacitor with the as-prepared Co3O4 nanowire arrays as a positive electrode and active carbon as negative electrode. All the unexceptionable supercapacitive behaviors illustrates that our unique 3D gully-network structure Co3O4 nanowire arrays hold a great promise for constructing high-performance energy storage devices.